Padrão de concorrência e estratégia competitiva: um estudo do Complexo Têxtil/Calçados - Crocco, Marco Aurélio (Nova Economia, 2013)
Padrão de concorrência e estratégia competitiva: um estudo do Complexo Têxtil/Calçados